Digital Transformation of the Integrated One-Stop Service at the Regional Office of the Ministry of Religious Affairs in Lampung through Data Integration and Automated Validation - Nurul Fajri (AMUYA: JOURNAL OF MANAGEMENT, 2026)
The transformation of public services through the online Integrated One-Stop Service (PTSP) system at the Regional Office of the Ministry of Religious Affairs in Lampung Province currently faces serious challenges regarding the uncertainty of service duration, caused by weak document verification systems. The primary issues identified include low data integration between work units (such as SIMKAH and EMIS data) and the absence of automated validation, which forces verifiers to perform repetitive manual checks, leading to document backlogs and bureaucratic inefficiency. This policy research utilizes a descriptive qualitative methodology with a content analysis approach toward related regulations and systematic observations of the existing digital workflow. The policy analysis is conducted using criteria of effectiveness, efficiency, and technical feasibility to evaluate various alternative solutions. The results indicate that the absence of a middleware layer and interoperability standards are the main obstacles to realizing a Digital Era Governance (DEG) ecosystem. Therefore, this policy paper recommends an acceleration strategy through the issuance of a Regional Head Instruction on Open API Implementation and the development of an integration infrastructure based on a Single Source of Truth (SSoT). The implementation of this solution is projected to automate up to 70% of the verification process, reduce the manual workload of verifiers, and ensure transparency through real-time document tracking features. By strengthening the theoretical foundations of Whole-of-Government and Agile Bureaucracy, this policy is expected to improve digital service quality (e-ServQual) and restore public trust in the professionalism of public services within the Ministry of Religious Affairs of Lampung Province.